Political participation patterns of the emerging middle classes in Peru and the Philippines - Babette Never; Chiara Anselmetti (German Institute of Development and Sustainability (IDOS), 2023)
The growing middle classes in middle-income countries may play a key role in current trends of democratic backsliding, online activism and lifestyle politics. This contribution uncovers which modes of political participation are prevalent among the middle classes in Peru and the Philippines, including new forms of online participation and lifestyle politics for sustainability. Drawing on household surveys conducted in 2018, we use latent class analysis and logit regressions to analyse, first, the characteristics of online vs offline participation, and second, the role of political consumption and online activism for political participation dynamics. The latter analysis contributes to the gateway/getaway debate of lifestyle politics. In both countries, we find four comparable classes: a substantial disengaged class that is not engaging in any political participation, an all-round activist class, an online activist class and a class that mostly engages in civil society activities. Further classes with specific participation patterns and socio-demographic characteristics could be identified for each country. Although the online activists in both countries are unlikely to engage in any other form of political participation, a clear empirical case for lifestyle politics as a separate mode of participation only exists among young Peruvians with a steady job. In the Philippines, political consumption as a form of lifestyle politics blends in with other types of political participation.
Keywords: 330; Political participation; online activism; lifestyle politics; political consumption; latent class analysis; middle class; democratic backsliding